Eksistensi Pendidikan Nahdlatul Ulama dalam Keberlanjutan Pendidikan Nasional - A. Fatikhul Amin Abdullah; Agung Dwi Bahtiar El Rizaq; Muhammad Hadiatur Rahman (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The lack of studies on Nahdlatul Ulama (NU) education in supporting national development goals obscures NU’s vision of realising a generation of Muslims who are intelligent, characterised, independent and morally good. This research aims to reconstruct the role of NU education in supporting the achievement of Sustainable Development Goals (SDGs) in the national education system. This research uses a historical qualitative design consisting of four stages, namely Heoristics, Criticism, Interpretation, and Historiography. The main results of this research describe that first, NU prioritises education as evidenced in the 4th NU congress in Semarang in 1929, a special institution was formed to handle NU Education under the name Hoof Bestur Nahdlatul Oelama (HBNO) in the Pergoeroean/Onderwijs section (now the Ma’arif NU Education Institute). Secondly, since the HBNO Onderwijs section was formed NU began to form several educational institutions from primary, secondary and higher education levels there are 54,274 out of a total of 399,378 educational institutions in Indonesia. Third, the transformation of NU education runs gradually, with adjustments to the times, without ignoring the principles of religious teachings and local culture.